2013
DOI: 10.1103/physrevlett.111.227201
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Control of Terahertz Polarization in a Multiferroic Manganite with Electromagnons

Abstract: All-electrical control of a dynamic magnetoelectric effect is demonstrated in a classical multiferroic manganite DyMnO3, a material containing coupled antiferromagnetic and ferroelectric orders. Due to intrinsic magnetoelectric coupling with electromagnons a linearly polarized terahertz light rotates upon passing through the sample. The amplitude and the direction of the polarization rotation are defined by the orientation of ferroelectric domains and can be switched by static voltage. These experiments allow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…This mode was previously found [54] to lower in energy for isotopically pure 65 CuO in comparison to 63 CuO, demonstrating that it results from an LA motion of Cu 2+ ions along (101), modulating the strongest superexchange interaction J 80 meV [31]. The three principal Raman modes were at the same energies for 65 CuO and 63 CuO, as expected for vibrations associated only with oxygen motion [54], while they shifted to lower frequencies for Cu 18 O than for Cu 16 O [59]. Further evidence for the magnetically induced zone folding of phonons in CuO was reported by Kuz'menko et al, who reported additional IR-active modes that were linked to phonon modes at the X and A points [51].…”
Section: Results: Ir-active Phononssupporting
confidence: 67%
See 2 more Smart Citations
“…This mode was previously found [54] to lower in energy for isotopically pure 65 CuO in comparison to 63 CuO, demonstrating that it results from an LA motion of Cu 2+ ions along (101), modulating the strongest superexchange interaction J 80 meV [31]. The three principal Raman modes were at the same energies for 65 CuO and 63 CuO, as expected for vibrations associated only with oxygen motion [54], while they shifted to lower frequencies for Cu 18 O than for Cu 16 O [59]. Further evidence for the magnetically induced zone folding of phonons in CuO was reported by Kuz'menko et al, who reported additional IR-active modes that were linked to phonon modes at the X and A points [51].…”
Section: Results: Ir-active Phononssupporting
confidence: 67%
“…Electromagnons-spin waves that become electric-dipole active in a magnetoelectric phase-are a recently discovered quasiparticle excitation that provide a window into the important spin interactions of magnetoelectrics [11][12][13][14][15][16][17]. The electric-field tuning of electromagnons in DyMnO 3 , an improper ferroelectric multiferroic [18], and of magnons in bulk BiFeO 3 , a proper ferroelectric multi-* j.lloyd-hughes@warwick.ac.uk ferroic [19], establish the potential of spin waves in data processing and communications [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, directional dichroism might reveal the character of the spin excitation observed in the THz spectra and identify whether it corresponds to a pure magnon or electromagnon, as in Ni 3 TeO 6 . Unfortunately, since the magnetic excitation lies below 8 cm -1 , more precise transmission measurements with a spectrometer based on backward-wave oscillator sources 39 and a crystal with diameter at least 10 mm would be required. In addition, using single crystals, one can avoid possible impurities often present at grain boundaries of polycrystalline samples, thus the anomaly seen at 23 K could be absent or better resolved.…”
Section: Spin and Lattice Excitationsmentioning
confidence: 99%
“…[184] Pimenov et al observed the new collective excitation corresponding to this multiferroic state known as electromagnon, i.e., electric-dipole active magnetic excitation in the imaginary part of the THz dielectric constant for GdMnO 3 and TbMnO 3 . [184,[187][188][189] This electromagnon has been reported as the rotational mode of the spiral spin plane which showed the absorption mode for E ω perpendicular to the plane of the spiral spin order. Such studies were further carried out with enhanced precision.…”
Section: Thz Studies On Multiferroic Rmnomentioning
confidence: 86%